2007
DOI: 10.1002/nau.20519
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of urinary nerve growth factor level with pathogenesis of overactive bladder

Abstract: These data suggest that urinary NGF levels could serve as a basis for adjunct diagnosis of OAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 32 publications
2
32
0
3
Order By: Relevance
“…Kim et al found that urinary NGF levels are increased in both men and women with OAB syndrome [20]. Yokoyama et al and associates evaluated urinary NGF in OAB patients and found that urinary NGF levels were elevated in neurogenic DO, spinal disease, and sensory urgency; however, urinary NGF was not found to be elevated in idiopathic DO [21]. It is rational to hypothesize that NGF produced in the urothelium and suburothelium can be secreted into the bladder lumen.…”
Section: Urinary Nerve Growth Factormentioning
confidence: 99%
“…Kim et al found that urinary NGF levels are increased in both men and women with OAB syndrome [20]. Yokoyama et al and associates evaluated urinary NGF in OAB patients and found that urinary NGF levels were elevated in neurogenic DO, spinal disease, and sensory urgency; however, urinary NGF was not found to be elevated in idiopathic DO [21]. It is rational to hypothesize that NGF produced in the urothelium and suburothelium can be secreted into the bladder lumen.…”
Section: Urinary Nerve Growth Factormentioning
confidence: 99%
“…OAB symptom and interstitial cystitis/painful bladder syndrome (IC/PBS) are prevalent urologic diseases that can cause considerable morbidity (Jacobs et al, 2010). However, the term OAB does not actually identify specific causes or disease entities (Yokoyama et al, 2008). Although the use of an urgency perception scale or urgency severity score has been suggested, these instruments are based on subjective reporting by the patient who must grade the degree of urgency and may be difficult for patients to understand the term of urgency (De Wachter and Wyndaele, 2003;Nixon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nerve growth factor is one of these stimulatory substances and is related to bladder hyperactivity. The urinary nerve growth factor levels in patients with neurogenic detrusor overactivity due to spinal cord injury, bladder outlet obstruction, and sensory urgency are significantly higher than those of subjects with normal cystometric findings [23] . Yoshimura et al [24] reported that chronic administration of nerve growth factor into the bladder or spinal cord of rats induced bladder hyperactivity.…”
Section: Discussionmentioning
confidence: 84%